A Puzzle of Microstructure Market Maker Models - Romeu, Rafael (IMF Working Papers; Working Paper ;, 2004)
This study addresses the empirical viability of microstructure models of dealer price setting. New evidence is presented rejecting these models' specifications of how information asymmetry and inventory accumulation affect dealer pricing. This rejection is consistent with those of other dealer-level empirical studies. This study suggests a new modeling option may be to reconsider optimal price setting while relaxing assumptions that specify incoming orders as the only component through which dealer inventories evolve. This approach is consistent with inventory evolution data and with general equilibrium models' assumptions about currency markets.